2.5 kW TMI-free co-pump Yb-doped fiber oscillator by 971.5 nm pumping wavelength. (January 2023) - Rezaei-Nasirabad, Reza; Azizi, Saeed; Paygan, Danial; Tavassoli, Mohammad; Abedinajafi, Ali; Roohforouz, Ali; Chenar, Reza Eyni; Golshan, Ali Hamedani; Hejaz, Kamran; Vatani, Vahid
Highlight: The power record of 2.5 kW for a co-pump oscillator with 20/400 µm fiber is attained by new pumping wavelength of 971.5 nm. The TMI-mitigating pumping wavelength of 971.5 nm is introduced and applied in the reported fiber oscillator configuration. TMI is strongly mitigated and SRS-induced mode instability appeared for the first time as the main obstacle in oscillators. Abstract: Pump wavelength shift from the peak absorption wavelength of 976 nm is one of the strategies for mitigation of transverse mode instability (TMI) in high-power Yb-doped fiber lasers. In the present contribution, 971.5 nm is introduced as an effective pumping wavelength for the increment of TMI threshold. By using this pumping wavelength, a 2580 W co-pumped fiber oscillator is built by 20/400 µm active fiber, with more than a twofold increase in the TMI threshold. Our analytical and experimental investigations indicate that due to the lower heat load of the pumping wavelength of 971.5 nm in the gain medium, it can properly mitigate TMI in fiber oscillators. Power scaling in here presented fiber oscillator is just limited to the occurrence of stimulated Raman scattering (SRS) induced mode instability and to the best of authors' knowledge, this is the first evidence of SRS-induced mode instability in high-power fiber oscillators and TMI is not the restricting factor in power scaling anymore.